Entomopathogenic potential of thermotolerant microorganisms isolated from infected Dermestes maculatus against Culex pipiens larvae - Boulanouar, Ali; Hamani, Zineb; Larbi, Benlarbi (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
During summer, when temperatures reach extreme records, the inhabitants Sahara seek refuge in oases for shade and water. These ecosystems are characterized by a unique microclimate. Nevertheless, they face serious threats from two arthropod species: venomous scorpions and mosquitoes, which act as vectors of diseases. Chemicals impacting both biotic and abiotic components of the ecosystem, and more critically human health. Chitinolytic entomopathogenic microorganisms were isolated from dust samples collected from the cadavers of the Dermestes maculatus. Chitin extracted from shrimp shells (yield: 16.6 %) served as the sole carbon source in the selective culture media employed for their cultivation. Five strains were obtained: three fungi (Aspergillus flavus, A. fumigatus, Mucor sp.) and two bacteria (Bacillus sp. and Actinomycete). Bioassays against third-instar Culex pipiens larvae showed that Actinomycete (10⁶ CFU.mL-1) induced 90 % of mortality, followed by A. fumigatus, Mucor sp., and Bacillus sp. (80 %), Data were analyzed using one-way ANOVA and Duncan’s test (p<0.05). Microscopic observations revealed severe larval deformities. These findings confirm the strong larvicidal potential of microorganisms as eco-friendly alternatives to chemical insecticides.